2018
DOI: 10.1080/10641963.2017.1288741
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of acute trans-resveratrol supplementation in treated hypertensive patients with endothelial dysfunction

Abstract: Endothelial dysfunction is a surrogate marker of cardiovascular risk. Resveratrol is known to improve endothelial function in animals, however, clinical trials are limited. We hypothesized that the acute trans-resveratrol supplementation improves endothelial function in treated hypertensive patients with endothelial dysfunction. Twenty-four hypertensive patients between 45 and 65 years-old with baseline endothelial dysfunction were enrolled in a randomized, cross-over, double-blind, placebo-controlled trial. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
4
40
0
2
Order By: Relevance
“…These results were in close concordance with an earlier trial conducted by the same group where a dose‐dependent effect of resveratrol on FMD was reported for the first time . Although the detailed mechanism of resveratrol's effect on FMD is not well defined, the vasodilatory effect of resveratrol is possibly delivered through an endothelial nitric oxide synthase‐3–mediated nitric oxide release in the endothelium …”
Section: Completed Clinical Trialssupporting
confidence: 91%
See 1 more Smart Citation
“…These results were in close concordance with an earlier trial conducted by the same group where a dose‐dependent effect of resveratrol on FMD was reported for the first time . Although the detailed mechanism of resveratrol's effect on FMD is not well defined, the vasodilatory effect of resveratrol is possibly delivered through an endothelial nitric oxide synthase‐3–mediated nitric oxide release in the endothelium …”
Section: Completed Clinical Trialssupporting
confidence: 91%
“…72 Although the detailed mechanism of resveratrol's effect on FMD is not well defined, the vasodilatory effect of resveratrol is possibly delivered through an endothelial nitric oxide synthase-3-mediated nitric oxide release in the endothelium. 73,74 An imbalance between insulin and glucagon can contribute to IGT and T2DM. 75 The glucagon hormone is produced by α cells in the pancreas and regulates the conversion of stored glycogen into glucose.…”
mentioning
confidence: 99%
“…Thirty studies reported measures of blood pressure, of which two were acute supplement studies and 28 were chronic (see Tables 5 and 6). Marques et al [106] showed no significant effect in systolic or diastolic blood pressure following acute administration of grape extract (600 mg). Wightman et al [101] also found no significant change in blood pressure with resveratrol alone (250 mg) or with resveratrol combined with piperine (250 mg + 20 mg).…”
Section: Effect Of Rwp On Blood Pressure In Humansmentioning
confidence: 95%
“…All remaining studies investigated the effects of red wine extract, grape extract, grape seed extract or some modification or combination of these. Five of the included studies investigated acute effects [101,106,110,122,132], whereas the majority looked at chronic supplementation, of which the most common length was 4 weeks (range = 2-52 weeks) [16-19, 27-31, 103-105, 109, 112-114, 116, 118, 119, 121, 124, 126-130, 134, 135]. To discern the potential differences between acute and chronic effects of RWP, these studies were separated for the purpose of analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation